Universal Electrospinning Scalable Plant for Filtering Nanofiber Production. (2017) - Solomin, E.V.; Sirotkin, E.A.; Sirotkin, A.A.
Abstract: The production of pure water free of contamination is an urgent issue again today and still is not completely solved. The usage of filtering nanofiber could be a solution to this problem. The article describes the electrospinning device for fabrication of filtering nanofiber material considering various electrospinning plant components. The electrospinning plant can be tuned to produce nanofibres with different characteristics. The main controlled parameters of the electrospinning plant are voltage on the capillary and the collector, the amperage, the distance between the capillary and the collector, collector rotational speed, and the supply solution intensity to the capillary. A filter nanofiber electrospinning method manufacturing technology and the results of the experiment and the dynamic characteristics of electrospinning process are described. Depending on the parameters of nanofiber we analyzed water filtration efficiency.